A biomechanical comparision of successful and unsuccessful triple-turn pirouette en dehors trials in ballet - Kim, J. (Texas Woman's University, College of Health Sciences, 2018)
Pirouette en dehors is a turn in which the dancer's body rotates and completes at least one full revolution with one foot on the floor. It is considered difficult to learn and perform in classical ballet. The purpose of this study was to identify biomechanical kinetic differences between the successful- and unsuccessful-trials groups in triple turn pirouette en dehors motion. It was hypothesized that the successful trials group would have larger longitudinal whole body angular momentum (AM), pivoting moment (PM) and ground reaction force moment (GRFM) than the unsuccessful trials group. Forty skilled collegiate or professional classic ballet dancers (11 males and 29 females) were recruited for this study. The participants were divided into two groups based on their successful and unsuccessful trials. Selected variables were computed through a seven-camera (Qualisys-three-dimensional) motion capture system (250 Hz) and two force-plates (Kistler-2500Hz), with 48 reflective markers. The data was imported into the Kwon3D (5.0) motion analysis software for subsequent data processing. Three MANOVA (SPSS 25.0) were used to compare the dependent variables between successful trials group and unsuccessful trials group conditions (each MANOVA was set p < .025). The first MANOVA was completed to compare all primary variables. The second MANOVA was performed to compare explanatory variables. The peak longitudinal AM, AM generation rate, and peak combined PM, gesture foot PM at TPM (time of peak PM) and gesture foot horizontal GRF at TPM were significantly different between the successful- and unsuccessful-trials groups. The successful trials group was characterized by larger whole body longitudinal AM, AM generation rate and peak PM, meaning this group demonstrated superiority in the generation of angular motion. The unsuccessful trials group had an inefficient double-to-single stance phase for the kinetic variables caused unsuccessful triple turn pirouette en dehors motion. While peak PM is lower for the unsuccessful trials group, a loss of whole body AM and AM rate creates a failed motion. Kinetics plays a major role in the performance of the triple-turn pirouette en dehors. Further investigation to compare kinematic variables for successful- and unsuccessful- trials group is warranted.